Cyclic Stretch Facilitates Myogenesis in C2C12 Myoblasts and Rescues Thiazolidinedione-Inhibited Myotube Formation - Chang, Ya-Ju; Chen, Yun-Ju; Huang, Chia-Wei; Fan, Shih-Chen; Huang, Bu-Miin; Chang, Wen-Tsan; Tsai, Yau-Sheng; Su, Fong-Chin; Wu, Chia-Ching (Frontiers in Bioengineering and Biotechnology, 2016)
Thiazolidinedione (TZD), a specific peroxisome proliferator-activated receptor r (PPARr) agonist, was developed to control blood glucose in diabetes patients. However, several side effects were reported that increased the risk of heart failure. We used C2C12 myoblasts to investigate the role of PPARs and their transcriptional activity during myotube formation. The role of mechanical stretch during myogenesis was also explored by applying cyclic stretch to the differentiating C2C12 myoblasts with 10% strain deformation at 1 Hz. The myogenesis medium (MM), composed of Dulbecco’s modified Eagle’s medium with 2% horse serum, facilitated myotube formation with increased myosin heavy chain and a-smooth muscle actin (a-SMA) protein expression. The PPAR protein and PPAR response element (PPRE) promoter activity decreased during MM induction. Cyclic stretch further facilitated the myogenesis in MM with increased a-SMA and decreased PPARr protein expression and inhibited PPRE promoter activity. Adding a PPARr agonist (TZD) to the MM stopped the myogenesis and restored the PPRE promoter activity, whereas a PPARr antagonist (GW9662) significantly increased the myotube number and length. During the myogenesis induction, application of cyclic stretch rescued the inhibitory effects of TZD. These results provide novel perspectives for mechanical stretch to interplay and rescue the dysfunction of myogenesis with the involvement of PPARr and its target drugs.